The Effect of Environmental Performance and Composition of Commissioners Board On Environmental Disclosure. - Muhammad Ahada; Unggul Purwohendi; Yunika Murdayanti (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
This study aims to examine the influence of Environmental Performance and Board Composition on Environmental Disclosure. This study used two independent variables and the dependent variable, Environmental Performance and Board Composition as independent variables, and Environmental Disclosure as the dependent variable. Environmental Performance is measured by using level of PROPER, Board Composition is calculated by proportion of independen commisioner, and Environmental Disclosure is measured by using environmental disclosure GRI G3. This study using secondary data, by using PROPER report and the annual report and also sustainability report that including the environmental information. Samples of this study consist of 24 company who join in PROPER and listed in Bursa Efek Indonesia during the period of 2011-2013.The data obtained by purposive sampling technique and using regression analysis method. Result from the model shows that: 1) Environmental Performance have a significant influence to Environmental Disclosure; 2) Board Composition have no significant influence to Environmental Disclosure 3) Simultaneus test, show that Environmental Performance and Board Composition have a significant influence to Environmental Disclosure. Keywords: Environmental Performance, Board of Commisioners Composition, Environmental Disclosure